Cup colour influences consumers’ expectations and experience on tasting specialty coffee - Carvalho, F; Spence, C (Elsevier, 2019)
The present study was designed to investigate the effect of the colour of the cup on sensory and hedonic judgments of specialty coffee by consumers. Altogether, 457 participants took part in one of three experiments. Crossmodal correspondences between the colour of the cup (i.e., an extrinsic cue) and the taste profile of the coffee served (i.e., the contents) were manipulated. Congruent and incongruent colour × taste pairings were created by using four cup colours (white, pink, yellow, and green) and two coffee profiles (sweet Brazilian and acidic Kenyan) to assess whether these manipulations would affect pre-and/or post-tasting ratings. Participants first rated their expectations of sweetness and acidity, and subsequently, their experience of those attributes on tasting the coffees, as well as rating their liking. The results revealed that the colour of the cup exerted a significant influence on both pre- and post-tasting ratings for all attributes measured. Liking ratings significantly decreased in incongruent pairing conditions – which also increased the unexpected acidity of the Kenyan coffee when tasted from the pink cup. Taken together, these results demonstrate for the first time that the colour of the cup significantly impacts sensory and hedonic judgements of specialty coffee. Our results also show that the contrast between expected and actual experience can result in a negative hedonic response and the enhancement of the unexpected sensory attribute. Implications for the development of coffee cups that can enhance the drinking experience are highlighted.